Vestibular dysfunctions in chronic brain ischemia in the post COVID period - Stoyanov, Alexander; Mashchenko, Serhii; Kalashnikov, Valeriy; Vastyanov, Rooslan; Pulyk, Alexander; Andreyeva, Tamara; Kolesnik, Olena; Стоянов, О.М.; Мащенко, С.С.; Калашніков, Валерій Йосипович; Вастьянов, Р.С.; Пулик, О.Р.; et al. (Wiadomości Lekarskie Medical Advances, 2023)
The aim: The aim of the study is the clinical-pathogenetic reasoning of vestibular dysfunctions (VD) development against the background of chronic brain ischemia in the presence of degenerative changes in the cervical spine (CS) in the post COVID period. Materials and methods: 82 patients, in the conditions of the clinical base of the Odessa National Medical University in 2019-2021 were examined. Group I with VD against the background of chronic brain ischemia (CBI) at the compensated phase; Group II with VD against the background of CBI at the subcompensated phase (33 men; 49 women), aged from 18 to 55 years. The control group (CG) consisted of 20 patients of the corresponding gender and age. The condition of the state of the autonomic nervous system, vestibular functions, cervical spine, cerebral arteries and emotional condition were examined. Results: Vestibulo-ataxic disorders were higher compared to CG and increased along with the degree of brain damage. An important aspect of the development of VD is autonomic dysfunction against the background of pathological autonomic characteristics with predominant parasympathetic orientation of autonomic tone, especially in the case of insufficiency of autonomic recativity (AR) and pathological autonomic support of activity. Such changes significantly increased in the presence of subcompensation of CBI. The correlation between psychoemotional disorders and changes in autonomic characteristics with VD against the background of CBI with initial regularities depending on the degree of brain damage was defined. The progression of CBI is facilitated by coronavirus infection and manifested in autonomic and psychoemotional dysfunctions. A characteristic hemodynamic feature in groups with compensated and subcompensated CBI is the presence of reduced perfusion in basilar (BA) and vertebral (VA) arteries. Changes in cerebral vascular reactivity with a decrease in cerebrovascular reactivity indicators were characteristic of the subcompensated phase of CBI. Hyperactivity to rotational functional loads in both clinical groups has a high correlation with the presence of stair descent and, to a lesser extent, isolated instability in CS. Conclusions: 1. The occurrence of VD is facilitated by the presence of autonomic dysfunction and degenerative-dystrophic changes in the CS, especially in case of subcompensation of CBI. 2. Psychoemotional changes were a characteristic feature of patients with VD against the background of CBI and had certain regularities depending on the phase of CBI. 3. Suffered coronavirus infection contributes to the progression of VD and further decompensation of CBI due to direct damage to the autonomic and vascular systems of the brain. 4. Changes in cerebral hemodynamics in the form of reduced perfusion in BA and VA, a decrease in cerebrovascular reactivity, and an increase in reactivity to rotational functional load were determined in patients with VD against the background of subcompensated CBI
Keywords: chronic brain ischemia; autonomic dysfunctions; degenerative-dystrophic damage; cervical spine; cerebrovascular reactivity; хронічна ішемія головного мозку; вегетативні дисфункції; дегенеративно-дистрофічні пошкодження; шийний відділ хребта; цереброваскулярна реактивність; 2023а